Fibule legionowe ze stanowiska w Kwiatkowie, gm. Brudzew. Uwagi na temat technik i technologii produkcji - Piotrowska, Magdalena; Rutkowski, Wojciech (Folia Praehistorica Posnaniensia, 2023)
The artefacts described in the paper come from the Przeworsk culture settlement in Kwiatków, where more than 100 fibulae were discovered. Among the artefacts acquired were three knee-shaped brooches with a semi-circular shield on the head. One of them was discovered in a well; the other two came from the surface of the site. This paper is mostly concerned with issues related to the technological aspects of the production of these items. In addition to the analysis of traces of craftsmanship found on the fibulae, XRF tests were performed to determine the material from which they were made. This approach allows one to supplement the typological findings and reconstruct the process of creating a given object. The brooches were microscopically examined for traces of craftsmanship. The attempt to determine the foundry method which had been applied failed to produce the expected results. Usually, individual instances of knee-shaped fibulae have been recorded at sites in Poland and other countries, such as the Czech Republic. In Kwiatków, however, the discovery contained as many as three such artefacts, though they had not been made in a workshop of one craftsman, although two display a high level of similarity.